2009
DOI: 10.1037/a0013998
|View full text |Cite
|
Sign up to set email alerts
|

Influences of sexual sensation seeking, alcohol consumption, and sexual arousal on women's behavioral intentions related to having unprotected sex.

Abstract: This experimental study examined effects of alcohol consumption and sexual sensation seeking on unprotected sex intentions, taking into account sexual arousal, indirectly discouraging sex, and condom insistence. Women (N=173; M age = 25.02) were randomly assigned to a control, placebo, low dose (target blood alcohol level = .04), or high dose (target blood alcohol level = .08) beverage condition. Participants projected themselves into a hypothetical sexual interaction with a man in which no condom was availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 37 publications
5
53
0
5
Order By: Relevance
“…Regarding the effects of sexual arousal, many studies have measured subjective or genital sexual arousal and found that individual differences in sexual arousal in response to arousing stimuli were associated with individual differences in the self-reported readiness to engage in unprotected sex (Abbey, Saenz, & Buck, 2005;Norris et al, 2009) or differences in self-estimated likelihood to sexually aggress in men (Davis, Norris, George, Martell, & Heiman, 2006a). Measured sexual arousal has also been found to mediate the effects of alcohol on the likelihood of agreeing to unprotected sex in men and women Prause, Staley, & Finn, 2011), women's rape myth acceptance (Davis, Norris, George, Martell, & Heiman, 2006b), and men's self-rated likelihood to sexually aggress (Davis et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effects of sexual arousal, many studies have measured subjective or genital sexual arousal and found that individual differences in sexual arousal in response to arousing stimuli were associated with individual differences in the self-reported readiness to engage in unprotected sex (Abbey, Saenz, & Buck, 2005;Norris et al, 2009) or differences in self-estimated likelihood to sexually aggress in men (Davis, Norris, George, Martell, & Heiman, 2006a). Measured sexual arousal has also been found to mediate the effects of alcohol on the likelihood of agreeing to unprotected sex in men and women Prause, Staley, & Finn, 2011), women's rape myth acceptance (Davis, Norris, George, Martell, & Heiman, 2006b), and men's self-rated likelihood to sexually aggress (Davis et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…It could also be that sexual sensation seeking may be shaped or influenced by the college atmosphere which is somewhat conducive to alcohol use, parties and lesser restrictions on sexual activities to a considerable extent, although sexual compulsivity may not be influenced to such an extent by college social environments. Studies have shown that sensation seeking is associated with increased alcohol consumption and unprotected intercourse (Cyder, Flory, Rainer, & Smith, 2009;Norris et al, 2009). Given that it has also been reported that young women may internalize more negative feelings after consuming alcohol than men (Gullette & Lyons, 2005), further investigations of the associations between sensation seeking, alcohol use and college women's sexual decision making process are warranted.…”
Section: Discussionmentioning
confidence: 97%
“…The second highest mean score was for the item "I like new and exciting sexual experiences and sensations" with a mean score of 2.75 (SD = 1.08). In this sample, adolescents tended to endorse statements that reflected a disposition for sexual sensation-seeking characteristics that are significant risk factors for higher levels of AOD use and related consequences (Norris et al, 2009).…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…However, it has been noted that they may play an important role in screening for high-risk adolescents with high scores on sexual sensation-seeking. Many studies have conceptualized sexual sensation-seeking as a distal risk factor for involvement in health risk behaviors (e.g., Kalichman et al, 2004, Norris et al, 2009. Consequently, fewer studies have proposed ways to induce behavioral change via the mechanism of modifying sexual sensation-seeking.…”
Section: Clinical Implications Of the Current Findingsmentioning
confidence: 99%
See 1 more Smart Citation